Environmental Compliance Control - Fitzmaurice, Malgosia (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The concept of environmental compliance control may be said to involve not just the development of new legal principles, but also a new attitude within the international community, as well as among governments and civil society at the national level, towards the governance of the global response to environmental challenges.
Keywords: kontrola zgodności; środowisko; zarządzanie